Encoded-Fusion-Based Quantum Computation for High Thresholds with Linear Optics - Song, Wooyeong; Kang, Nuri; Kim, Yong-Su; Lee, Seung-Woo (American Physical Society, 2024)
We propose a fault-tolerant quantum computation scheme in a measurement-based manner with finite- sized entangled resource states and encoded-fusion scheme with linear optics. The encoded fusion is an entangled measurement devised to enhance the fusion success probability in the presence of losses and errors based on a quantum error-correcting code. We apply an encoded-fusion scheme, which can be performed with linear optics and active feedforwards to implement the generalized Shor code, to construct a fault-tolerant network configuration in a three-dimensional Raussendorf-Harrington-Goyal lattice based on the surface code. Numerical simulations show that our scheme allows us to achieve up to 10 times higher loss thresholds than nonencoded fusion approaches with limited numbers of photons used in fusion. Our scheme paves an efficient route toward fault-tolerant quantum computing with finite-sized entangled resource states and linear optics.